Penerapan Permainan Kooperatif terhadap Perkembangan Sosial Emosional Anak Usia Dini - hanna choirunnisa aziz; Rizawati (Universitas Lancang Kuning, 2022)
Cooperative games are games related to social communication in a team and encourage the emergence of a togetherness and cooperation of children. Socio-emotional development is a child's development that needs to be stimulated, because it will affect the child's future life, especially when interacting with the environment around the child. This study aims to determine the effect of cooperative games on social emotional development, using research methods (classroom action research) with a population of